Adaptation of the eyewitness metamemory scale into Turkish: a validity and reliability study - Aydın, Aylin (The Bulletin of Legal Medicine, 2025)
Objective: This study aims to adapt the Eyewitness Testimony Metamemory Scale into the Turkish language and to assess its validity and reliability for use in Turkish-speaking communities. The scale was developed to measure individuals’ awareness of their memory capacity for eyewitness accounts. Methods: The study recruited 201 participants. Statistical methods including exploratory factor analysis and confirmatory factor analysis were used to assess the construct validity of the scale. Cronbach alpha coefficient was calculated to assess the reliability of the scale. The original Eyewitness Metamemory Scale was translated into Turkish and culturally adapted following rigorous methodological guidelines. Results: Exploratory and confirmatory factor analyses revealed that the construct validity of the scale was robust. In addition, Cronbach’s alpha coefficient showed that the scale had a high level of internal consistency. These results support that the Turkish version of the Eyewitness Metamemory Scale is a psychometrically reliable and valid measurement tool. Conclusion: The Turkish Eyewitness Metamemory Scale has been evaluated as an appropriate and reliable tool for assessing individuals’ memory awareness in eyewitnessing contexts in Turkey. This scale provides an important tool for both research and practical applications.